Music education right on track - The Star, (2012)
Music education in the country is on the right track with more focus given to creativity and innovative ness, said Deputy Information, Communications and Culture MinisterDatuk Maglin Dennis D'Cruz. He said the teaching staff in the music field had been playing a big role in producing music talents and in fact, works that could be the country's treasures.